2006
DOI: 10.1159/000092485
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C – A Marker for Assessment of the Glomerular Filtration Rate in Patients with Cisplatin Chemotherapy

Abstract: Background: Cystatin C has recently been proposed as an ideal marker for glomerular filtration rate (GFR). In this study, cystatin C serum levels were evaluated in comparison to serum creatinine concentrations and inulin clearances in patients with normal kidney function receiving cisplatin-based chemotherapy to assess the validity of cystatin C as an alternative endogenous marker of GFR. Methods: Blood samples for the assessment of cystatin C, creatinine and inulin clearances were collected in patients before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 22 publications
(10 reference statements)
1
37
2
1
Order By: Relevance
“…These equations also appear to offer limited precision (52,110,113,116,124,129,130). As we shall see below, they could be more useful in certain subpopulations in which creatinine-based equations are particularly inaccurate, as in paediatrics (116,117,124), transplantation (113,115,(131)(132)(133) or oncology (134). Validation studies on large independent populations, however, would appear to be needed.…”
Section: Gfr Measurement Algorithms Incorporating Cyscmentioning
confidence: 99%
See 3 more Smart Citations
“…These equations also appear to offer limited precision (52,110,113,116,124,129,130). As we shall see below, they could be more useful in certain subpopulations in which creatinine-based equations are particularly inaccurate, as in paediatrics (116,117,124), transplantation (113,115,(131)(132)(133) or oncology (134). Validation studies on large independent populations, however, would appear to be needed.…”
Section: Gfr Measurement Algorithms Incorporating Cyscmentioning
confidence: 99%
“…In addition, as this study included renal failure patients (inulin clearance between 43.6 and 115.1 mL/min) it is impossible to compare the serum cystatin concentrations found with reference values in the literature (134).…”
Section: Cysc and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…6 In recent years, data have shown that cystatin C, a cysteine protein kinase inhibitor, determines GFR more accurately. [7][8][9] Cystatin C is constituted of 120 amino acids and belongs to the cystatin superfamily. It is found in a constant concentration in all cells with nucleus and is excreted to the blood stream.…”
Section: Introductionmentioning
confidence: 99%